The micro-credentials approach to Higher Education - Arroyave Villa, Norberto Alonso (Rastros Rostros, 2023)
The changes generated by the third and fourth industrial revolution in all sectors of society also impact the educational ecosystems, especially tertiary education, which, after assuming a more active role in the economic development of nations, has adopted new dynamics in its system based on the generation of lifelong learning and the design of personalized and non-linear learning paths that benefit employability. The purpose of this article is to explore the micro-credentialing approach as a complementary strategic trend in university programs that favors the new dynamics in demand. First, a literature review is carried out to take a look at the origin of this strategy, its characteristics, conditions, methodology, criticisms, projections and recommendations. Then, some good practices led by universities worldwide and locally concerning its use are described, and finally, the potential of the ucc to include microcredentialing in its learning pathways is detailed. The analysis shows that, despite the lack of unified regulatory policies, the strategy has been widely deployed, especially in Europe and North America, and that Colombia has joined the Latin American countries that have seen in it an opportunity to serve a wider training public and stimulate demand for their academic programs. This constitutes an opportunity for the ucc, which has sufficient theoretical, institutional, and methodological inputs to implement it because it fits perfectly with its institutional vision.